Research of hafnium-containing defects in granular nickel EP741NP alloy using electron microscopy - I. N. Trunkin; M. A. Artamonov; A. V. Ovcharov; A. L. Vasiliev (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2019)
In the process of low-cycle fatigue testing of blanks of turbine disks of turbojet engines made of granular EP741NP nickel alloy, fracture samples were obtained. The fracture area was examined by various electron microscopy methods. Accumulation of rounded high-hafnium micro-particles was detected in the center of the fracture according to the data of energy-dispersive X-ray microanalysis. Such clusters are observed in about half the instances of fractures in similar blanks. Hafnium is an alloying element, but its content is strictly limited and should not exceed 0.4 mass %. Elucidation of the nature of the formation of this type of defects is a subject of scientific and practical interest. Using high-resolution transmission electron microscopy, energy-dispersive X-ray microanalysis and electron diffraction, it was determined that these particles are monoclinic single crystal $HfO_2$ structures. Some particles contain nuclei that differ in their elemental composition and structure. Some of the nuclei contain C, O, S, F, etc. that may be indicators of organic contamination of the sample. A high-carbon amorphous shell was found around some $HfO_2$ particles. The data obtained indicate that the formation of these particles is associated with organic contaminations. To prevent the formation of such centers of destruction, it is necessary to improve the purity of the technological processes of production.